THE EFFECT OF PERSONAL ENGINEERING ABILITY, TRAINING AND EDUCATION, UTILIZATION OF TECHNOLOGY, AND WORK EXPERIENCE ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS - Bambang Sugiharto; Trisandi Eka Putri; Anestya Hayatunufus Hafsyah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
This study aims to determine whether there is an influence of personal technical ability, training and education, the use of technology, and work experience on the effectiveness of the accounting information system. The data used in this study is primary data by distributing questionnaires in the form of google forms and questionnaires. The method used in sampling is a non-probability sampling method with purposive sampling technique and the number of samples in this study were 115 respondents, who were employees of the Yogya Group in Subang Regency. The data was processed using the data quality test method, classical assumption test, multiple regression analysis, and hypothesis testing. The results of this study indicate that the variables of training and education, and the use of technology have a positive effect on the effectiveness of accounting information systems. While the variables of personal technical ability and work experience have no effect on the effectiveness of accounting information systems.